RISK FACTORS FOR PERI-IMPLANTITIS IN THE POSTERIOR FIXED IMPLANT-PROSTHETIC THERAPY: RETROSPECTIVE STUDY - Davidescu Alexandra; Norina Forna; Doriana Agop-Forna; Cristina Dascălu; Ana-Maria Fătu; Scutariu Mihaela-Monica (Romanian Journal of Oral Rehabilitation)
Aim. The goals of this research were to determine the risk factors and predictors of peri-implantitis in patients with implant-supported posterior fixed prosthetic restorations. Materials and method. The logistic regression was performed within a cohort of 48 patients (mean age 63.04 ± 10.723 years) with posterior edentulism treated by implant-supported metal-ceramic fixed prosthetic restorations. Socio-demographic data (gender, age group) and anamnestic data were collected on: smoking status; periodontal grade; compliance to the supportive periodontal/peri-implant therapy; OHI index. Clinical and radiological parameters were measured in 166 implants to establish the status of the peri-implant tissues in relation to analysed parameters. Results. 45.8% of patients and 19,9% of implants were diagnosed with peri-implantitis. Conclusions. In univariate models, patients with in age group 40-60 yrs., males, smokers, periodontitis grade III (vs. I) and grade IV (vs. II), OHI 2-3, have an increased risk of peri-implantitis. In multivariate analysis, significant predictors of peri-implantitis were male gender, OHI 2-3, maxillary location, grafted implant sites.